Singles [videorecording (DVD)] - Crowe, Cameron, 1957-; Crowe, Cameron, 1957-; Fonda, Bridget; Scott, Campbell; Sedgwick, Kyra; Kelley, Sheila; True-Frost, Jim; Pullman, Bill; Dillon, Matt (Warner Home Video, 1999)
This tale of Seattle twentysomethings searching for-- and running from-- love centers around a romantically aloof rocker and his lovestruck neighbor who hopes to get him to change his tune.